Three-Dimensional Tetrathiafulvalene-Based Covalent Organic Frameworks for Tunable Electrical Conductivity - Li, Hui; Chang, Jianhong; Li, Shanshan; Guan, Xinyu; Li, Daohao; Li, Cuiyan; Tang, Lingxue; Xue, Ming; Yan, Yushan; Valtchev, Valentin; Qiu, Shilun; Fang, Qianrong (Journal of the American Chemical Society, 2019)
The functionalization of three-dimensional (3D) covalent organic frameworks (COFs) is essential to broaden their applications. However, the introduction of organic groups with electroactive abilities into 3D COFs is still very limited. Herein we report the first case of 3D tetrathiafulvalene-based COFs (3D-TTF-COFs) with non- or 2-fold interpenetrated topology and tunable electrochemical activity. The obtained COFs show high crystallinity, permanent porosity, and large specific surface area (up to 3000 m /g). Furthermore, these TTF-based COFs are redox active to form organic salts that exhibit tunable electric conductivity (as high as 1.4 × 10 S cm at 120 °C) by iodine doping These results open a way toward designing 3D electroactive COF materials and promote their applications in molecular electronics and energy storage.